Answer:
1/59049
Step-by-step explanation:
Answer:
a) y = -5 b) y = -4 c) y = 4 d) y = 11
Step-by-step explanation:
a) (-2+2)²-5
b) (-1+2)²-5
c) (1+2)²-5
d) (2+2)²-5
This seems like a lot more work than it is, but here we go
Simplifying<span>8 + -2y = 3y + -2
Reorder the terms: 8 + -2y = -2 + 3y
Solving 8 + -2y = -2 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right.
Add '-3y' to each side of the equation. 8 + -2y + -3y = -2 + 3y + -3y Combine like terms: -2y + -3y = -5y 8 + -5y = -2 + 3y + -3y
Combine like terms: 3y + -3y = 0 8 + -5y = -2 + 0 8 + -5y = -2 Add '-8' to each side of the equation. 8 + -8 + -5y = -2 + -8
Combine like terms: 8 + -8 = 0 0 + -5y = -2 + -8 -5y = -2 + -8 Combine like terms: -2 + -8 = -10 -5y = -10
Divide each side by '-5'. y = 2
Simplifying y = 2</span><span>
</span>
Let's solve your equation step-by-step.
2x
/5 + 3 = x/10 - 1
Step 1: Simplify both sides of the equation.
2x
/5 + 3 = x/10 - 1
2/5x + 3 = 1/10x - 1
Step 2: Subtract 1/10x from both sides.
2/5x + 3 - 1/10x = 1/10x - 1 - 1/10x
3/10x + 3 = -1
Step 3: Subtract 3 from both sides.
3
/10x + 3 - 3 = -1 - 3
3/10x = -4
Step 4: Multiply both sides by 10/3.
(10/3) * (3/10x) = (10/3) * (-4)
x = -40/3